Protecting biodiversity in our national parks: proposing a regional communication strategy for the National Park Service - Hollman, Shelby (Kansas State University, 2020)
The mission of the National Park Service is to “preserve unimpaired the natural and cultural resources and values of the national park system for the enjoyment, education, and inspiration of this and future generations. The park service cooperates with partners to extend the benefits of natural and cultural resource conservation and outdoor recreation throughout this country and the world (National Park Service 2019a).” The influx of tourism and lack of funding has left parks struggling to balance tourism with conservation efforts based upon a review of National Park Service budget allocations (The United States Department of the Interior 2019). Conservation management is mandated nationally from the government and parks take this information and apply it within the individual park boundaries and coordinate with their respective state governments (National Park Service 2019a). From communication with the National Park Service concerning biodiversity conservation efforts within the parks, there seems to be no mandated strategy to manage projects regionally. Even though there is communication happening between parks regarding certain research efforts, not all the park staff can easily communicate with staff from other parks. This study examines biodiversity conservation strategies in the Intermountain Region including Glacier, Yellowstone, Grand Teton, Rocky Mountain National Parks, and their partners in addition to national parks in other countries like Canada and Australia. Through qualitative research, including document analysis and interviews, the findings revealed a few key ideas centered around improving graphic communication on the park service website and increasing connection between key stakeholders. The result of the findings is a strategy focused on a regional communication network that connects the National Park Service with donors, partners, researchers, educators, volunteers, and the public through an online portal. The network also provides a way to organize projects by type. Examples of network implementation include a proposed website and an annual report featuring key projects for the National Park Service. The outcome of this research is a report, from an outsider’s perspective, for the National Park Service to consider improving communication efforts between the National Park Service, their partners, and the public. The report is intended to make the parks’ biodiversity conservation efforts more visible in order to protect them, and potentially promote greater financial sponsorship and volunteerism from visitors to better protect the natural environment in an era of budget shortfalls.
Keywords: National Park Service; Intermountain Region; Biodiversity conservation; Communication network